Criação de um tool box para o software ADVISOR com a arquitetura paralela de eixos separados - Rodrigues, Julio Cesar Bortolini (2021)
Faced with factors such as global warming, increased pollution, the need for transportation, among others, governments and society together promote regulations and programs to reduce society’s impacts on the environment. Among the adopted initiatives, we can mention the efforts made by scientists in the research to develop energy storage systems with higher energy density and higher power density, and also seeking a solution that is less impactful on the environment. In this work, the objective is to create a toolbox for the ADVISOR software with the architecture of a parallel hybrid electric vehicle with separate axles. Changes were made to the block diagram of the PARALLEL_defaults_in architecture, present in the library of that software, changes that enabled the implementation of the objective proposed in this work. During the execution of this project, the problem of not using energy from regenerative braking arose. To solve this adversity, adjustments to the block diagram responsible for the equations related to energy regeneration through braking were necessary. The simulations were carried out by submitting each of the two vehicular structures to the NBR6601 urban driving cycle, considering that each architecture is capable of complying with the design parameters. The results showed a greater energy efficiency for the VEH Parallel-ES, presenting a positive point for this configuration.